Biomass models for young planted Norway spruce and naturally regenerated silver birch, aspen and rowan trees - Jaakko Repola; Jaana Luoranen; Saija Huuskonen; Mikko Peltoniemi; Päivi Väänänen; Karri Uotila (Silva Fennica)
We developed tree level biomass (dry weight) models for Norway spruce (Picea abies [L.] H. Karst.), silver birch (Betula pendula Roth), rowan (Sorbus aucuparia L.) and aspen (Populus tremula L.) growing in young spruce dominated seedling stands with high mixture of broadleaves. The study material was collected from three planted Norway spruce seedling stands located on mineral soil in southern Finland. Biomass models were estimated by individual tree component (stem, living branches, foliage, stump, and roots with diameter of 2 mm) by using a multi-response approach (seemingly unrelated regression), which estimated the parameters of the sub-models (tree component) simultaneously. Even though the application and generalization of the developed models can be restricted by the limited material, they provide new information of seedling biomass allocation and more reliable biomass predictions for spruce and birch growing in young seedling stand compared with those of the commonly applied biomass models (Repola 2008, 2009) in Finland. Repola’s models (2008, 2009) tended to produce biased predictions for crown and below-ground biomasses of seedlings by allocating too much biomass to roots and too little to needle and branches. In addition, this study provides biomass models for aspen and rowan, which were not previously available.